PERAWATAN LUKA PADA KORBAN GEMPA DI KP. CIPETIR, DESA CIWALEN, KEC. WARUNGKONDANG CIANJUR, PROVINSI JAWA BARAT - Juairiah Juairiah; Dea Aprilya; Rini Rahmasari (JPS : Jurnal Pengabdian Serulingmas, 2023)
Geologically, Indonesia is in a disaster-prone area, because Indonesia is located on three tectonic plates in the world, namely: the Indo-Australian Plate in the south, the Euro-Asian Plate in the north and the Pacific Ocean Plate in the east so that Indonesia is at high risk of experiencing earthquakes. Earthquakes can damage various infrastructure and endanger lives. One of the earthquakes that occurred in Cianjur, West Java Province resulted in many victims, especially in Kp. Cipetir, Ciwalen Village, Kec. Warungkondan who suffered minor to serious injuries because of being crushed by the ruins of the building. Update data on injured victims from the